The effect of participatory budgeting on the performance of government officials (An empirical study in West Lombok District) - Mohammad Fachrizal; Lalu Suparman; Animah . (Universitas Hayam Wuruk Perbanas, 2016)
This study aimed to examine effects of three intervening variable directly and indirectly, that are job relevant information, budget goal commitment, and job satisfaction on relationship between budgetary participation and apparatus performance. The inconsistencies of the previous research of the effect of the budgetary participation on the performance become the motivation of the present research. The present research is a survey in which data were collected using a questionnaire distributed to the SKPD Structural Officials of consisting of Echelon II, Echelon III and Echelon IV at the Regional Government of West Lombok Regency. The populations are 673 persons structural officials of Echelon II, Echelon III and Echelon IV. Respondents was selected by purposive sampling method in which officers involved in the budgeting process, of the 122 distributed questionnaires, all questionnaires were returned. The analysis method was variant-based SEM using SmartPLS Version 2.0 M3. The instruments have been examined for its validity and reliability. The results show that the budgetary participation has influence with the apparatus performance but not significant, the budgetary participation has significant effect on job relevant information, job relevant information has significant effect on the apparatus performance, budgetary participation has significant effect on budget goal commitment, budget goal commitment has significant effect on the apparatus performance, budgetary participation has significant effect on job satisfaction, and job satisfaction has significant effect on the apparatus performance. The research could prove the budgetary participation has correlation with the apparatus performance through job relevant information, budget goal commitment, and job satisfaction. The implication of this research that the increased performance of the apparatus can be done by increasing the budgetary participation through job relevant information, budget goal commitment, and job satisfaction.